Salicylic acid influences the protease activity and posttranslation modifications of the secreted peptides in the moss Physcomitrella patens. (21st December 2018) - Filippova, Anna; Lyapina, Irina; Kirov, Ilya; Zgoda, Victor; Belogurov, Alexey; Kudriaeva, Anna; Ivanov, Vadim; Fesenko, Igor
Abstract : Plant secretome comprises dozens of secreted proteins. However, little is known about the composition of the whole secreted peptide pools and the proteases responsible for the generation of the peptide pools. The majority of studies focus on target detection and characterization of specific plant peptide hormones. In this study, we performed a comprehensive analysis of the whole extracellular peptidome, using moss Physcomitrella patens as a model. Hundreds of modified and unmodified endogenous peptides that originated from functional and nonfunctional protein precursors were identified. The plant proteases responsible for shaping the pool of endogenous peptides were predicted. Salicylic acid (SA) influenced peptide production in the secretome. The proteasome activity was altered upon SA treatment, thereby influencing the composition of the peptide pools. These results shed more light on the role of proteases and posttranslational modification in the "active management" of the extracellular peptide pool in response to stress conditions. It also identifies a list of potential peptide hormones in the moss secretome for further analysis. Abstract : In this study, we performed a comprehensive analysis of the whole extracellular peptidome using moss Physcomitrella patens as a model. Hundreds of modified and unmodified endogenous peptides that originated from functional and nonfunctional protein precursors were identified. The plant proteases responsible for shaping the pool of endogenous peptides were predicted. These results shed more light on the role of proteases and posttranslational modification in the "active management" of the extracellular peptide pool in response to stress conditions.